Marine plastic debris as a reservoir and vector of antibiotic-resistant pathogens: evidence of transmission to sea turtles in the Southwest Indian Ocean - Philippe Jourand; Alice Philippe; Loris Carret; Shiva Moutoucomarapoule; Celia Crespel; Leila Leon; Loik Sababadichetty; Margot Thibault; Clarisse Majorel; François Guilhaumon; Véronique Lenoble; Claire Jean; et al. (Marine Environmental Research, 2026)

Do loggerhead sea turtle (Caretta caretta) gut contents reflect the types, colors and sources of plastic pollution in the Southwest Indian Ocean? - Margot Thibault; Ludovic Hoarau; Laurent Lebreton; Matthieu Le Corre; Mathieu Barret; Emmanuel Cordier; Stéphane Ciccione; Sarah-Jeanne Royer; Alexandra Ter Halle; Aina Ramanampamonjy; Claire Jean; Mayeul Dalleau (Marine Pollution Bulletin, 2023)

Differential methylation between sex in adult green sea turtle skin biopsies - Benjamin Mayne; Walter Mustin; Vandanaa Baboolal; Francesca Casella; Katia Ballorain; Mathieu Barret; Mathew A. Vanderklift; Anton D. Tucker; Oliver Berry (Frontiers in Marine Science, 2023)
In marine turtles, the sex of hatchlings is determined by their egg incubation temperature. Global warming may increase the extinction risk by skewing hatchling sex ratios. Assessment of this risk at the population level requires the identification of sex in hatchlings and juveniles. However, available methods are typically lethal, highly invasive, or difficult to conduct at a large scale. Changes in DNA methylation, an epigenetic modification, have been characterized as part of sex differentiation pathways in some species with environmentally determined sex, but so far not in marine turtles. Neither have epigenetic biomarkers for sex been developed into rapid assays suited to research on wildlife. In this study, we aimed to develop a rapid, minimally invasive, and inexpensive method to identify the sex of marine turtles. We used reduced representation bisulfite sequencing DNA methylation data from adult green sea turtle ( Chelonia mydas ) skin biopsies to identify 16 genomic regions exhibiting differential methylation between males and females (adjusted p-value < 0.01). We designed methylation sensitive qPCR assays for these regions and tested their capacity to identify the sex of turtles ranging in age between 3-34 years. The qPCR assay identified the correct sex in turtles > 17 years. However, the sex of younger turtles could not be accurately identified. This suggests the sex differences distinguishable by the assay were adult specific, reflecting the training data on which the sex-specific regions were identified, and likely linked to late-stage ontogenetic changes associated with sexual maturity. Epigenetic biomarkers are a promising tool for wildlife research because they can be minimally invasive and high throughput. Future research into sex-specific differentially methylated regions in hatchlings and juveniles should be based on genome-wide DNA methylation data from a wider age range, which includes hatchlings.

Isotopic niche partitioning of co-occurring large marine vertebrates around an Indian ocean tropical oceanic island - Guillaume Chandelier; Jeremy J. Kiszka; Violaine Dulau-Drouot; Claire Jean; Thomas Poirout; Vanessa Estrade; Mathieu Barret; Jacques Fayan; Sébastien Jaquemet (Marine Environmental Research, 2023)